Kajian Hadis-hadis Palsu yang Populer oleh Ustadz Adi Hidayat - Atika Yulanda (Islam Transformatif : Journal of Islamic Studies, 2020)
Hadith is the second teaching of Islam after the Koran. The Hadith contains all the words, deeds and provisions of the Prophet Muhammad. But sometimes those traditions do not originate from the Prophet and are called false traditions. The rise of fake but popular hadith in the community is very alarming. With the rise of false traditions that are contrary to the teachings of Islam it is expected for Muslims to always hold fast to the values of the Koran and As Sunnah so as not to stray far from Islamic teachings. With the study of traditions that are not only fixated on the books and books of traditions such as the study of traditions on YouTube is very easy for humans. Existing hadith studies provide positive values and an understanding of the science of traditions for seekers of hadith studies. For example, studies of fake hadiths are rife in public life delivered by a well-known Ulama and graduates from abroad as well as experts in the science of traditions such as Adi Hidayat. The false traditions conveyed are related to the phenomena that exist in society. The explanation related to the false traditions in social media is very interesting and makes it easy for the hadith seekers to find the criteria of fake traditions and examples of fake traditions. The fake hadith according to Adi Hidayat is anything that does not originate from the Prophet and his narrators are liars and cannot be trusted such as the hadith of cleanliness in part from the faith. That is an example of a false but popular tradition.